Autoimmune Hepatitis - Serena Longhi, Maria; Mieli-Vergani, Giorgina; Vergani, Diego (Current Pediatric Reviews, 2014)
Autoimmune hepatitis (AIH) is a severe hepatopathy characterised by female preponderance, hypertransaminasaemia, elevated levels of immunoglobulin (IgG), presence of serum autoantibodies and, histologically, by interface hepatitis. AIH occurs both in adults and children, being particularly aggressive in the latter. According to the type of serum autoantibodies, AIH can be differentiated in two forms: one positive for smooth muscle antibody (SMA) and/or antinuclear antibody (ANA) (type 1 AIH, AIH-1) and another positive for liver kidney microsomal antibody type 1 (LKM-1) (type 2 AIH, AIH-2). These two forms differ with regard to age at onset (earlier in the case of AIH-2), mode of presentation (fulminant hepatic failure more frequently observed in AIH-2) and association with IgA deficiency (more frequent in AIH-2). AIH responds satisfactorily to immunosuppressive treatment (corticosteroids with or without azathioprine) that should be started as soon as the diagnosis is made. Despite immune suppression, some 40% of patients experience relapse and 9% undergo liver transplantation. Though the exact mechanism leading to loss of immune-tolerance in AIH is still unclear, recent evidence has pointed to a numerical and functional defect of CD4posCD25pos regulatory T-cells as a factor permitting autoaggressive CD4 and CD8 T-cells to react against liver autoantigens. The generation and expansion of regulatory T-cells with liver autoantigen specificity in vitro represents a potential immunotherapeutic tool for the reconstitution of immune-tolerance in AIH without the drawback of pan-immunosuppression.
Keywords: regulatory T-cells